Validation of Sliding Mode and Passivity Control in High-Power Quadratic Buck Converter Through Rapid Prototyping - Rafael Antonio Acosta-Rodriguez; Fredy Hernan Martinez-Sarmiento; German Ardul Munoz-Hernandez; Gerardo Mino-Aguilar; Edgar Alfredo Portilla-Flores; Paola Andrea Nino-Suarez; Octavio Jose Salcedo-Parra (IEEE Access, 2024)
This document introduces a rapid control prototyping (RCP) approach applied to the industrial sector using a non-linear Quadratic Buck Converter (QBC) DC-DC. The goal is to reduce manufacturing costs for materials and electronic devices while enhancing the power quality in the system’s response. An experimental setup is utilized to create a functional model, converting 380 VDC to 48 VDC at a power level of 500 W. dSPACE CP1103 is employed to implement Model in the Loop (MIL), Software in the Loop (SIL), and Hardware in the Loop (HIL) simulations. Modern control techniques, including sliding mode control (SMC) and passivity-based control (PBC), are employed to devise a robust control scheme capable of maintaining stability in real-time (RT) and resisting disturbances. The document concludes with a performance analysis, PI, Cp, CpK, Z-score, and ITAE considering response time, signal accuracy, system stability, and resource utilization efficiency.